2005
DOI: 10.25336/p6b304
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Premarital Cohabitation on Marital Stability over the Duration of Marriage

Abstract: Research has shown that premarital cohabitors who eventually marry are more likely to divorce or separate than persons who do not cohabit prior to marriage. This study investigates the possibility that the difference in marital stability between cohabitors and non-cohabitors may change with increasing duration of marriage. Using Canadian 1995 General Social Survey data, various Proportional Hazards Models were specified to compare the marital dissolution risks of cohabitors and non-cohabitors, while controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Consistent with studies done in other countries, for instance Ghana (Takyi, 2001) and Canada (Budinski & Trovato, 2005), one of the interesting substantive finding of this study is that having children in a marriage or union increases the cost of marital or union dissolution. A study conducted using 1993/94 Ghana Demographic and Health Survey (GDHS-93) data indicated that the propensity for union dissolution declined with increasing number of children (Takyi, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with studies done in other countries, for instance Ghana (Takyi, 2001) and Canada (Budinski & Trovato, 2005), one of the interesting substantive finding of this study is that having children in a marriage or union increases the cost of marital or union dissolution. A study conducted using 1993/94 Ghana Demographic and Health Survey (GDHS-93) data indicated that the propensity for union dissolution declined with increasing number of children (Takyi, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…The growing tolerance of cohabitation as a stage in the marriage process has made it a conventional step in the process of marriage, as has been demonstrated in the United States and sub-Saharan Africa (Budinski & Trovato, 2005;Mokomane, 2005). This argument is based on the premise that couples use cohabitation, rather than traditional engagement, as a phase to test for compatibility in a relationship, thus improving marital stability (Oppenheimer, 1988;Budinski & Trovato, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Budinski and Trovato (2005). Results from this study show that the relationship between age and union status is different between women and men.…”
Section: Marital Unions and Unmarried Cohabitation In Bangkokmentioning
confidence: 79%